Improved food functional properties of pea protein isolate in blends and co-precipitates with whey protein isolate. (April 2021) - Kristensen, H.T.; Denon, Q.; Tavernier, I.; Gregersen, S.B.; Hammershøj, M.; Van der Meeren, P.; Dewettinck, K.; Dalsgaard, T.K.
Abstract: Much attention has been drawn to the utilization of plant proteins as food ingredients because of an increasing demand for protein-rich foods with improved nutritional and functional properties. One method to meet these exigencies is co-precipitation. The aim of this study was to evaluate solubility, foaming and emulsification properties of whey protein isolate (WPI) and pea protein (PPI) blends and understand the impact of co-precipitation. Co-precipitates and protein blends in parallel ratios were compared and functional properties were studied at pH 3, 7 and 11.5. The functional properties increased at higher pH. Overall, PPI hampered the functional properties. Co-precipitation improved the functional properties of PPI, where samples with WPI > PPI showed promising results. Improvements could also be obtained by simply blending of PPI and WPI. In fact, protein blends were superior in solubility and foaming capacity, while no significant difference could be obtained for foam stability and emulsifying properties. Thus, the results demonstrate that co-precipitation is not a necessity to partly replace animal proteins in food formulations with plant protein. Graphical abstract: Image 1 Highlights: Foam and emulsion properties of whey protein-pea protein co-precipitates and blends were studied. Co-precipitation improved the functional properties of PPI significantly. Solubility and foaming properties of protein blends were superior to co-precipitates. Emulsifying properties showed no difference between co-precipitate and blends.